Virucidal Efficiency of Chemical Agents: A comparative Analysis (Bangladesh Journal of Microbiology, 2016)
Present study was designed to explore the influences of different categories of chemical factors, such as organic solvents, oxidizing agents, anionic detergent and dye on persistence of locally isolated coliphages and shigaphages from clinical sewage samples. Thirty percent ethanol initiated 83.20 and 62.86% reduction in the number of coliphage and shigaphage plaques in our study respectively. Chloroform mediated decrease in our observation was 53.13 and 88.33% for coliphages and shigaphages, respectively. The number of the shigaphage plaques was reduced by 62.5% following biphasic diethyl ether (DEE) treatment. About 72.66% of coliphages were deactivated after exposure to biphasic diethyl ether. Exposure of the isolated coliphages and shigaphages to 1% formalin had completely destroyed the viability of the bacteriophages. Coliphage survival in this investigation was 37.5% and 2.4% following treatment with 0.3 and 3.0% hydrogen peroxide respectively. The decrease in overall coliphage and shigaphage population was 95.83% and 94.14% while treated with 0.5% sodium dodecyl sulfate (SDS). The number increased for the viruses infecting E. coli by 9.52% where the number of shigaphages declined by 14.63% while growing in presence of a divalent cation [Ca(NO3)2]. Coliphage and shigaphage populations were diminished by 61. 76% and 53.48% respectively after treatment with the neutral red (0.0075%) followed by exposure to visible light.Bangladesh J Microbiol, Volume 31, Number 1-2,June-Dec 2014, pp 47-52